2006
DOI: 10.1177/1534735406291984
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Andrographis paniculata and Andrographolide on Cyclophosphamide-Induced Urothelial Toxicity

Abstract: The protective effect of Andrograhis paniculata and andrographolide (ANDLE) against cyclophosphamide (CTX)-induced urothelial toxicity was investigated in this study. Pretreatment of Swiss albino mice with A paniculata extract (10 mg/dose/animal intraperitoneally [ip]) and ANDLE (500 µg/dose/animal ip) could significantly reduce CTX (1.5 nmol/kg body weight)-induced urothelial toxicity. Morphological and histopathological analysis of urinary bladder of CTX-treated mice showed severe inflammation and dark color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…A recent report by Sheeja and Kuttan 41 showed that cyclophosphamide-induced urothelial toxicity in mice via reactive oxygen species production and treatment with ANDLE resulted in elevated levels of GSH in the liver and bladder of cyclophosphamide-treated mice. Nitric oxide is a highly reactive free radical associated with the severity of cyclophosphamide-induced bladder injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report by Sheeja and Kuttan 41 showed that cyclophosphamide-induced urothelial toxicity in mice via reactive oxygen species production and treatment with ANDLE resulted in elevated levels of GSH in the liver and bladder of cyclophosphamide-treated mice. Nitric oxide is a highly reactive free radical associated with the severity of cyclophosphamide-induced bladder injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is a highly reactive free radical associated with the severity of cyclophosphamide-induced bladder injury. 41 Administration of ANDLE has been shown to reduce the level of nitric oxide metabolite and protect mice from cyclophosphamide-induced urinary bladder injury. 41 The results of the present study suggest that the antioxidative effect of ANDLE may be due to its ability to activate antioxidant enzymes that catalyze the reduction of oxidants and that its use for recovery of hepatic damage may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide (Sheeja and Kuttan, 2006), berberine, curcumin, isothiocyanates (Manesh and Kuttan, 2005), mesna, protein A, GSH, squalene (Senthilkumar et al, 2006), and 2 -mercaptopropionyl glycine have shown varying degrees of protection against CTX toxicity. It has also been reported that many plant extracts such as Andrographis paniculata (Sheeja and Kuttan, 2006), Ayurvedic Rasayana, Cassia occidentalis , Emblica officinalis , garlic, Ixora coccinea, Juglans regia (Haque et al, 2003), Phyllanthus amarus (Kumar and Kuttan, 2005), Tinospora cardiofolia, and Withania somnifera (Davis and Kuttan, 2001), have exhibited ameliorating effects on CTX toxicity. This demonstrates that plant extracts have great potential in reducing the toxicity of CTX and the search for other such agents is vital to the management of side effects of CTX.…”
Section: Introductionmentioning
confidence: 98%
“…Recently in China, Cy is being used in combination with various detoxifying and protective agents with the purpose of enhancing the efficacy and reducing the toxicity, such as many traditional Chinese medicinal herbs, Cassia occidentalis (Bin-Hafeez et al, 2001), Phyllanthus amarus (Kumar and Kuttan, 2005), Andrographis paniculata (Sheeja and Kuttan, 2006). Combining Chinese medicinal herbs with chemotherapy may improve quality of life, tumor response and performance status, as well as reduce the toxicity of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%